FRI0381 Pattern of Clinical Presentation and Outcome of Polymyalgia Rheumatica. (15th July 2016) - Sobrero, A.; Camellino, D.; Cosso, C.; Pizzorni, C.; Cutolo, M.; Cimmino, M.A.
Abstract : Background: Polymyalgia rheumatica (PMR) is an inflammatory disorder of the elderly characterized by girdle pain and stiffness, constitutional symptoms and elevation of inflammatory indexes. Glucocorticoid (GC) treatment is effective but often prolonged, with associated side effects. Data on risk factors of poor prognosis are scanty: in particular it is not known if the pattern of clinical presentation can influence PMR outcome. Objectives: To test the hypothesis that clinical presentation of PMR can predict its outcome. Methods: 394 patients (251 women, median age 73 yrs, range 47–92 yrs) with PMR diagnosed according to Bird's criteria, visited between 1990 and 2014 by the same clinician were studied. Median follow up was 13.8 months (range 1–250 months). Clinical features recorded at disease presentation included involvement of: i) the shoulder girdle; ii) the pelvic girdle; iii) the column; vi) two or more of the previous locations; v) with giant cell arteritis (GCA); or vi) with acute onset, defined as completion of full symptoms and signs in ≤72h. PMR outcome was evaluated by considering: i) duration of follow-up; ii) appearance of peripheral arthritis; iii) appearance of GCA; iv) number of exacerbations/ relapses; v) cumulative dosage of GC; vi) use of methotrexate (MTX); and vii) death. Results: At multivariate analysis, acute onset predicted a longer follow-up duration (p=0.007) and death (p=0.037); involvement of the spine predicted longer follow up duration (p=0.001) and use of MTX (p=0.018); presentation at the pelvic girdle predicted a high number of exacerbations/relapses (p=0.034) and association therapy with MTX (p=0.009); onset in multiple locations predicted a high number of exacerbations/relapses (p=0.03); presentation with GCA predicted a higher cumulative dosage of GC (p=0.0001) and use of MTX (p=0.027). Conclusions: Apart from the obvious association between concomitant GCA and negative prognosis of PMR, other clinical characteristics at disease onset influence outcome. In particular, the initial presentation with multiple locations, including spine and pelvic girdle, resulted in longer follow-up, more relapses, and need of MTX treatment, whereas the classic one with only shoulder girdle involvement was associated with a milder disease. An acute onset was also a negative prognostic factor. Clinicians should consider the pattern of disease presentation when evaluating the burden of PMR. Disclosure of Interest: None declared